Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan - Alviannoor, Alviannoor; Fahrati, Eny (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to determine how economic growth, human development index (HDI), and unemployment on poverty levels in South Kalimantan in 2010-2019. The method used in this research is the method of multiple linear regression with the help of software Eviews 9. This type of research is quantitative descriptive with secondary data in panel data obtained from the Central Statistics Agency of South Kalimantan. Therefore, the most appropriate model in this study is the random effect model. The study results by testing the partial regression coefficient (t-test) with α = 5% showed the HDI and unemployment variables significantly influence poverty levels. Furthermore, simultaneous results (F test) with α = 5% indicate that together with economic growth, HDI and unemployment variables significantly affect poverty levels. The most influential variable in this study is the HDI. For poverty to fall faster, the HDI needs more attention in making policies. As for the education factor, the 12-year compulsory education program is free of charge. Health, by improving facilities and infrastructure in each Posyandu and Puskesmas. Expenditure by maintaining purchasing power (inflation) and increasing public income.